1990
DOI: 10.1126/science.248.4958.975
|View full text |Cite
|
Sign up to set email alerts
|

Radar Reflectivity of Titan

Abstract: The present understanding of the atmosphere and surface conditions on Saturn's largest moon, Titan, including the stability of methane, and an application of thermodynamics leads to a strong prediction of liquid hydrocarbons in an ethane-methane mixture on the surface. Such a surface would have nearly unique microwave reflection properties due to the low dielectric constant. Attempts were made to obtain reflections at a wavelength of 3.5 centimeters by means of a 70-meter antenna in California as the transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(54 citation statements)
references
References 24 publications
1
53
0
Order By: Relevance
“…Additionally, if the surface is as radar rough as the icy Jovian satellites, the echo energy is expected to be broadly spread to the full Doppler width. The initial experiments determined that, indeed, the echo was broad and thus that the surface is radar rough (Muhleman et al (1990). Several attempts were made to detect the echo from Titan using the Goldstone monostatic radar, and a reasonable Doppler spectrum was obtained after averaging over several days, verifying the broad limb-to-limb spreading of the echo (RM Goldstein RF Jurgens, private communication, 1992).…”
Section: Titanmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, if the surface is as radar rough as the icy Jovian satellites, the echo energy is expected to be broadly spread to the full Doppler width. The initial experiments determined that, indeed, the echo was broad and thus that the surface is radar rough (Muhleman et al (1990). Several attempts were made to detect the echo from Titan using the Goldstone monostatic radar, and a reasonable Doppler spectrum was obtained after averaging over several days, verifying the broad limb-to-limb spreading of the echo (RM Goldstein RF Jurgens, private communication, 1992).…”
Section: Titanmentioning
confidence: 99%
“…Echoes from Titan were first obtained in June, 1989 by Muhleman et al (1990) using the VLA/Goldstone radar configuration. The diameter of Titan (5150 Km) subtends an angle of just 0.89 arc see at 8 AU, which can barely be resolved with the VLA in its largest configuration at a wavelength of 3.5 cm.…”
Section: Titanmentioning
confidence: 99%
“…The first efforts to detect Titan with ground-based radar were made in 1989 (Muhleman et al, 1990) using the Goldstone 3.5 cm wavelength radar transmitter with reception of the echoes at the Very Large Array, imaging the echo power in the opposite (OC) and same (SC) circular senses relative to the transmitted polarization. That and subsequent experiments through 1992 (Muhleman et al, 1993) found Titan's reflectivity to be moderately high with an average of 0.22 in the OC polarization sense, but with large uncertainties.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the emission from Saturn's atmosphere is probably the simplest to model and the disk-integrated emission is easily observed from Earth. Distant Titan radiometer and scatterometer observations can also provide reference data for calibration since Titan has also been observed by radar systems on the Earth [2]- [5]. The Huygens probe has provided a temperature measurement on the surface [6], and this may provide the best absolute calibration reference of all.…”
Section: F Calibration Observationsmentioning
confidence: 99%